Decomposing US Income Inequality à La Shapley: Race Matters, but Gender Too - Frédéric Chantreuil; Kévin Fourrey; Isabelle Lebon; Therese Rebiere (Institute of Labor Economics (IZA), 2020)
This paper is an application of a new Shapley income decomposition methodology, in which we isolate two subjective factors in income differences - race and gender - that contribute to income inequality within the population of blacks and whites in the United States over the period 2005-2017. We show that the purely racial contribution to income inequality as defined by the Gini index varies from 1% to 4% depending on the geographical administrative divisions used. Race tends to contribute more to inequality in the Western and Southern part of the country. Whatever the division, the share of income inequality associated with gender exceeds greatly that of race. While gender income inequality falls over time, income inequality associated with race tends to increase.
Keywords: C71; D63; J15; J71; 330; income inequality; decomposition; Shapley value; racial discrimination; gender discrimination